Effectivity of Probiotic Bacteria in Feed on Growth and Survival Rate of Common Carp (Cyprinus carpio) - Nurbety Tarigan; Firat Meiyasa (Universitas Gadjah Mada, 2019)
The aim of this study was to examine the effectiveness of the commercial bacterial probiotic addition in feed on growth and survival rate of common carp. This research was conducted from July to September 2018. This study used a completely randomized design (CRD) with four treatments and three replications. The initial body length of juveniles was 5-6 cm with density 1 juvenile/litersfor 42 days. In this research, we used different dosages of commercial probiotics 0, 5, 10 and 15 ml/kg. The results showed that the administration of those probiotics in the feed had a significant effect on the relative growth rate, survival rate, efficiency of feed utilization, and protein efficiency ratio on carp juvenile. Administration of probiotics at 15 ml/kg is the best treatment for a relative growth rate 2.96%, survival rate 100%, efficiency of food utilization 72.07%, and protein efficiency ratio 12.19%. In conclusions, probiotics mixed in feed are able to increase the digestibility of feed so that it supports the growth and survival rate of common carp.